Surgical Management of Gorlin Syndrome. Issue 4 (April 2015) - Griner, Devan; Sutphin, Daniel; Sargent, Larry A.
<x xml:space="preserve">Abstract</x> Abstract Basal cell nevus syndrome (aka Gorlin syndrome, Gorlin-Goltz syndrome, nevoid basal cell carcinoma syndrome, and fifth phacomatosis) is a rare but well-described autosomal dominant condition with variable penetrance. We present a female patient who has been successfully treated using local surgical excision and diligent skin surveillance for more than 4 decades, demonstrating that simple local incision is an efficacious and reasonable surgical alternative that may circumvent the specialization and expense of Mohs technique.